Pedagogical Content Knowledge Components' Integration in Teaching Biology using IBA: Grade 8 Teachers' Case Study - Garcia, Lea C (Alipato, A Journal of Basic Education, 2023)
Though pedagogical content knowledge (PCK) has been investigated in a variety of study fields, its impact has received little attention since the Department of Education imposed the inquiry-based approach (IBA) during the 2016 K-12 implementation. A type of knowledge that is specific to teachers, PCK is based on how teachers connect their pedagogical knowledge to their subject matter knowledge. Through PCK, teachers can create inquiry classrooms that can strengthen students’ scientific reasoning and understanding. The PCK components (content, student’s understanding, instructional strategies, and assessment) may be integrated into teaching science as IBA is used. This study looks at how teachers use IBA to demonstrate the mentioned PCK components integration as well as determine the impact of the integration. Based on the school’s implementation of IBA and other IBA-related activities, a sample of two beginning and two experienced Grade 8 teachers were chosen. Data were evaluated by in-depth PCK analysis and triangulation involving validation through cross-verification using classroom observations, interviews, and other instructional resources. Beginning teachers integrated the various PCK components more frequently than experienced teachers. Integration impact included cognitive activation and students’ conceptual understanding improvement. Future studies on PCK components integration, IBA mentoring and continuing professional development programs are recommended.